حوكمة الزكاة في الدول الإسلامية: دراسة مقارنة بين ماليزيا وتركيا وإندونيسيا لتعزيز الكفاءة والعدالة الاجتماعية - Abdul Hamid, Mohamad; Muneeza, Aishath; Hardani, Ali (Al Urwah : Sharia Economics Journal, 2025)
This study aims to analyze and compare the zakat management and regulatory systems in Malaysia, Turkey, and Indonesia by examining the legal, administrative, and technological frameworks of each model and identifying the challenges and opportunities for improving zakat fund distribution efficiency. The study employs a descriptive-analytical and comparative approach, collecting data from secondary sources, including academic literature, government reports, and zakat-related regulations in each country. The findings reveal that Malaysia adopts a centralized system supported by digital technology, enhancing transparency and efficiency. In contrast, Turkey follows a decentralized model based on non-governmental organizations, but it lacks a unified regulatory framework. Meanwhile, Indonesia employs a hybrid model, combining government supervision with non-governmental participation, providing greater flexibility but facing challenges in coordination and oversight. Based on these findings, the study recommends enhancing cooperation between government and non-governmental institutions, increasing the use of technology in zakat fund management, standardizing legal frameworks, raising public awareness, and developing an integrated monitoring system to ensure fairer and more efficient distribution. Implementing these recommendations can contribute to strengthening the role of zakat in economic and social development, making it a more effective tool for poverty alleviation and achieving social justice in Islamic countries.